The impact of self-awareness on leadership behavior - Peter Hartung (Journal of Applied Leadership and Management, 2020)
Research questions: Does self-awareness influence the effectiveness of leadership with regard to employee motivation and satisfaction or employee productivity? Methods: Literature research to evaluate current findings on contemporary leadership models, personality traits, emotional intelligence and self-awareness; data for hypothesis testing was collected anonymously via an online version of the Leadership Tasks Survey during May - December 2019 (N = 255); examination methods included descriptive statistics, exploratory factor analysis and correlation analysis. Results: Very low overall research volume on self-awareness and leadership behavior, 127 existing studies confirm strong positive impact; the default survey data set (N = 255) was modified to conform to normality (N = 102). Exploratory factor analysis on the modified data set revealed a latent four-factor structure; Pearson correlation analysis revealed significant correlations for the self-awareness constituents morale and self-transparencywith other LTS items.
Keywords: 650